1-(1,3-Benzodioxol-5-yl)ethanone - Jasinski, Jerry P. (International Union of Crystallography, 2010)
In the title compound, C(9)H(8)O(3), the dihedral angle between the mean planes of the benzene and dioxole rings is 1.4 (8)°, with the dioxole group in a slightly distorted envelope configuration with the flap C atom displaced by 0.0645 Å from the plane through the other four atoms. In the crystal, weak intermolecular C—H⋯O hydrogen-bond interactions link the molecules into chains propagating in [011]. The crystal packing exhibits weak π–π interactions as evidenced by the relatively short distances [3.801 (9) Å] between the centroids of adjacent benzene rings.